Stronger bilateral efferent influences on cochlear biomechanical activity in musicians than in non-musicians - Perrot, Xavier; Micheyl, Christophe; Khalfa, Stéphanie; Lionel Collet (Neuroscience letters, 1999)
The auditory sensory end organ is under the control of the central nervous system via efferent projections. Contralateral suppression of otoacoustic emissions (acoustic signatures of the cochlear biomechanical activity) provides a non-invasive approach to assess olivocochlear efferent activity in humans. Using this approach, the present study compared professional musicians with musically-inexperienced subjects. The results revealed stronger bilateral cochlear suppression, suggesting larger efferent influences in both ears, in musicians. Furthermore, in indicating no difference in left/right asymmetry of efferent-mediated suppression between the two groups, the present findings suggest that the observed differences in olivocochlear activity reflect bilaterally-enhanced activity of the cortical auditory structures in musicians rather than differences in cerebral hemispheric asymmetry between the two groups.